(3cGed GdUfGYI GdWHjIs - (3GdeLhSj, Ydqj Hf YHGS, fMh (B400 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdHGH GdChd aj UOQ GdcJGH CMHHJ Cf CUfa Edi NRGfJg cJGHG cGedG aj UfGYI GdWH LGeYG deG jMJGL Edjg GdeJWHHhf hZjQge ef MaX GdUMI Ydi GdCUMGA hQOgG Ydi GdeQVi EP cfJ de CLO s
(3BNQgG (B:s
(3hPdc Cf efJgi gPg GdCeQGV hMQcJgG JHWF eGOJgG hGdYdGeGJ ajgG dG JXgQ aj GdCjGe GdChd hJJCNQ HMSH ebOGQ Whd GdeQV hcPdc jfHZj Cf JJabO CMhGdgG aj cd fhY JeJ GdebGdI GdYGTQI hGdLRA GdYdej s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B4 \ 297s
(3cTa GdXfhf (B2 \ 1380s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdWHs